Analisis Kepadatan Tanah dengan Pengujian California Bearing Ratio (CBR) - Kamil, Firmanilah (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2022)
Soil density must be considered because of climate change and increasingly extreme weather. This is possible to cause things that are not desirable. The research was conducted in three stages, namely preparation, testing, and data analysis. Samples were taken at 10 points in Ketapang Regency. The data processing carried out showed that the wet soil density value in the sample soil was 1.05 gr/cm3 to 1.94 gr/cm3. The value of dry density in the sample soil is from 1.01 gr/cm3 to 1.88 gr/cm3. The value of water content in the sample soil is 16.01% to 41.87%. The CBR value obtained from testing with the CBR-test on the sample soil is 0.01% to 10.30%